Effects of stream intermittency on minnow (Leuciscidae) and darter (Percidae) trophic dynamics in an agricultural watershed. Issue 3 (19th December 2021) - Fallon, Christine E.; Capps, Krista A.; Freeman, Mary C.; Smith, Chelsea R.; Golladay, Stephen W.
Abstract: Stream intermittency is predicted to increase where water withdrawals and climate warming are increasing. In regions coupled with high fish diversity, understanding how intermittency influences fish trophic ecology is critical for informing ecosystem function. This study compared fish diets across seasons in perennial and intermittent streams to estimate the immediate and cumulative effects of stream drying on fish foraging patterns. We used gut content analysis to compare the diets of small‐bodied, secondary consumer fishes, including two minnow and three darter species found in the lower Flint River Basin of southwestern Georgia, during both the summer (before stream dry‐down) and fall (post flow resumption) seasons. Fish communities in perennial streams had greater diet richness compared to fishes in intermittent streams for both seasons. Darter diets were characterised by rheophilic aquatic insects in perennial streams and by benthic crustaceans (copepods, cladocerans and isopods) and predatory aquatic insects in intermittent streams. Minnow diets were typified by freshwater sponges, eggs and organic detritus in intermittent streams and by terrestrial insects and diatoms in perennial streams. Fishes in intermittent streams consumed significantly more benthic crustaceans in the fall (37% increase in proportional volume) compared to preflow cessation conditions in the summer, suggesting these organisms play an important, yet relatively unrecognised role in supporting fish communities in southeastern streams. Our findings enhance our understanding of how stream intermittency influences the trophic dynamics of secondary consumer fishes in an agricultural watershed increasingly affected by water scarcity.